EVALUASI DAMPAK BANGUNAN SEMENTARA ARRIVING SHAFT PADA PEMBANGUNAN TEROWONGAN PENGENDALI BANJIR (SUDETAN) KALI CILIWUNG KE KANAL BANJIR TIMUR - Indah Handayasari; Hamzah Mujahid (KILAT, 2015)
One alternative solution handling the flood planned by the Government of DKI Jakarta is to do the construction of flood control tunnel or commonly called the sudetan to maintain the stability of the river volume or time so that the flood overflow does not occur. However the construction of flood control tunnel or sudetan done on implementation process must pay attention to the impact that may arise given the tunnel built under the surface of the ground and the surroundings of the housing of the population. The results of the study indicate the movement of land that occurs along the southern Shaft Arriving by 5 cm and a decrease in elevation advance groundwater during construction of Shafts Arriving 49,3 cm. However, both ground movement of face elevation and decrease in groundwater that occurs is still within the safe and does not affect the structure of the buildings around the site of the work so that the retaining walls of soils can function properl.